Review of HVDC systems for enhancing resilience after extreme natural events. Issue 11 (23rd July 2021) - Luo, Chuhang; Liang, Liang; Bai, Xiaoyang
Abstract: Compared with AC systems, HVDC systems are more flexible and potentially contribute to enhancing system resilience. Currently, three types of HVDC technologies, LCC‐HVDC (Line‐commutated Current‐sourced Converters, LCC), VSC‐HVDC (Voltage Sourced Converter, VSC), and MMC‐HVDC (Modular‐Multilevel‐Converter, MMC), are applied in practical projects. All types of HVDC systems can be applied to stabilize the system frequency of AC power systems and facilitate system recovery after extreme natural events. The operation characteristics, methods, and control strategies of different HVDC technologies for facilitating system operation are reviewed herein; it is indicated that HVDC technology is an effective solution for enhancing system resilience. Renewable resources, energy storage systems, and demand response devices can be coordinated well with HVDC systems. The frequency and voltage regulation ability of power systems and the black start ability can be enhanced by introducing HVDC systems into power systems. Several isolated AC power systems can be connected to HVDC systems. These AC systems can interact with other AC systems through HVDC systems by conforming to their operational characteristics and constraints. The resilience of these AC systems can be enhanced by these interactions. Additionally, related operation methods and control strategies will also be reviewed.